Pengembangan Media pembelajaran berbasis mobile pada mata pelajaran jaringan dasar di SMKN 5 Padang - Reza Oktaliardi; Heri Mulyono; Irsyadunas Irsyadunas (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2021)
At least the use of learning media in SMK N 5 Padang and lessons only focus on what the teacher teaches so that students reduce student interest in learning. This study aims to produce a learning media with basic network subjects at SMKN 5 Padang that are valid and practical. This study uses the Research and Development method with the IDI development model covering 3 stages, namely Define, Develop and Evaluate. The population “in this study were students of class X TKJ at SMK N 5 Padang totaling 25 students, the sampling technique used total sampling and data collection techniques in the” form of questionnaires. The results of the assessment from media experts with an average of 0.9 valid categories, and assessments from material experts with an average of 0.87 valid categories. “The results of the practicality test by the teacher” with “a percentage” of 0.9% “in the very practical category, and the” students' practicality results with an average of 85.56% “in the very practical category